Photocatalytic oxidation of methanol using titanium dioxide/single-walled carbon nanotube composite - C. Dechakiatkrai (2018)
Titanium dioxide/single-walled carbon nanotube (TiO2 /SWNT) composites were prepared for photocatalytic applications. The composites were characterized using UV-visible and Raman spectroscopy, zeta-potential measurements, cyclic voltammetry coupled with a photoreactor, scanning electron microscopy, and transmission electron microscopy coupled with energy dispersive X-ray spectroscopy. The photocatalytic activity of TiO2 and the TiO2 /SWNT composite was investigated using the photo-oxidation of methanol in sulfuric acid as supporting electrolyte. The results indicate that the TiO2 /SWNT composite enhances the photocatalytic activity compared to TiO2 alone. Electrochemical studies of the TiO2 /SWNT composite were also carried out in various supporting electrolytes and the presence of SWNTs was shown to increase the current achieved in voltammetric measurements. © 2007 The Electrochemical Society.